KAKAWIN ARJUNA WIWĀHA: KAJIAN TEOLOGI HINDU - Ida Made Windya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Kakawin Arjuna wiwāha is an Old Javanese literary work written in the XI century AD by Mpu Kanwa. In general Arjuna wiwāha contains teachings about reaching the perfec- tion of life. This concept of perfection of life in Arjuna wiwāha was analyzed by using the concept of Hindu Theology. The teachings of the perfection of life are explained in Kakawin's literary form which encompasses the whole life based on human creativity, taste, and intention. Creativity refers to a logical structure to obtain the value of truth, feeling refers to an aesthetic structure to ob- tain the value of beauty, and intention refers to an ethical structure to obtain value of morality. The theological concept in Arjuna wiwāha is divided into four parts, namely: Beliefs about God, beliefs about self, beliefs about the world, and beliefs about the after life (sunya). The results of the study will reveal the divine teachings in Kakawin Arjuna wiwāha, the teach- ings of yoga as a way to reach God, the concept / nature of human identity, the teachings of karma phala, and the function of Kakawin Arjuna wiwāha.